Web Application Training with Hypermedia Engineering to Increase Global Marketing Competitiveness of Decorative Umbrella Industry - Sulistyanto, Hernawan (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This service activity is intended for a group of people to empower economic independence (management aspects) and improve skills (hard skills and soft skills) (educational aspects) in the dimensions of strengthening promotions and improving marketing models for ornamental umbrella industry production in the Klaten area. The form of activity is in the form of training on web application design based on hypermedia engineering. A target audience is a group of craftsmen, namely groups of productive people who work as ornamental umbrella craftsmen in Klaten. The main problem found based on empirical observations in the field is that there is currently no more modern marketing model available to promote and market umbrella production worldwide. The main consequence of this is that product marketing has stalled so that it has an impact on the accumulation of product results among craftsmen. This has implications for abundant production stock so it is very detrimental in the calculation of the production process which in the end makes many craftsmen stop their business. One of the efforts to overcome this is by improving the promotion model and marketing tools through the use of hypermedia navigation technology. The main target of this activity is to empower and improve the skills of craftsmen in marketing products using modern web applications through hypermedia engineering. Activities are debriefing and in the form of training carried out using lecture, demonstration, exercise, and mentoring methods. The lecture method is used to activate the spirit of entrepreneurship and competition, as well as to explain the concept of online marketing and hypermedia technology. The demonstration method is used to demonstrate a work and learning process, namely the stages of designing and installing a modern web application with hypermedia, as well as presenting examples of how to pioneer a form of global promotion and marketing. Meanwhile, the training method is used to practice how to design and manage promotional content for marketed products and interconnect them in interactive hypermedia navigation. While the mentoring method will provide opportunities for participants (craftsmen) to consult directly and continuously in overcoming obstacles that arise during the training process and early implementation of hypermedia applications. Based on the activities that have been carried out, several conclusions can be drawn, namely a significant increase in the ability to master web applications and online marketing of the craftsmen and the potential for increasing product marketing on a global scale. The main obstacle in this activity is the low awareness of the craftsmen to increase their potential and competence.